Effect of maternal corticosteroid provision on middle cerebral artery peak systolic velocity readings in the potentially anaemic fetus prior to planned intrauterine transfusion. Issue 1 (11th October 2019) - Urutherakumar, Varshinee; Henry, Amanda; Welsh, Alec
Abstract: Purpose: Middle Cerebral Artery Peak Systolic Velocity (MCA‐PSV) is the main tool for determining need for and timing of intrauterine transfusions (IUT) for severe fetal anaemia. It has been suggested that steroids temporarily decrease MCA‐PSV, potentially increasing false‐negative MCA‐PSV findings in anaemic fetuses. We therefore aimed to assess whether maternal corticosteroid administration prior to IUT is associated with clinically significant temporary decreases in MCA‐PSV. Methods: Retrospective review 2005–2016 of steroid provision prior to IUT, with correlation of MCA‐PSV pre‐ and post‐steroid administration and haemoglobin at IUT. Results: In 23 identified cases, there was no significant difference between average MoM pre‐ and post‐steroid (1.71 ± 0.41 vs. 1.66 ± 0.38, −2.9% mean, P = 0.4). There was also no significant difference between pre‐ and post‐steroid MoM taken within 3 days of each other (n = 19, P = 0.21). However, post‐steroid MCA‐PSV decreased by >15% in 6/23 cases (A‐B zone in two cases, B‐C zone in one case). Conclusions: This study found no sizeable, generalised effect of corticosteroid administration on MCA‐PSV readings in the potentially anaemic fetus. A minority showed substantial shifts where reliance on post‐steroid MCA‐PSV could have unfavourably altered clinical management. Ultimately, further large‐scale research is required before we can discount the potential impact of steroids on MCA‐PSV values.